Reduced adaptive thermogenesis during acute protein-imbalanced overfeeding is a metabolic hallmark of the human thrifty phenotype. Issue 4 (5th July 2021) - Hollstein, Tim; Basolo, Alessio; Ando, Takafumi; Krakoff, Jonathan; Piaggi, Paolo
ABSTRACT: Background: The human thrifty phenotype is characterized by a greater decrease in 24-h energy expenditure (24EE) during fasting due to relatively higher eucaloric 24EE in sedentary conditions, both of which are indicative of greater propensity to weight gain. Thriftiness is also associated with a smaller increase in 24EE (i.e., reduced adaptive thermogenesis) during overfeeding. Objectives: We investigated whether short-term measures of adaptive thermogenesis during overfeeding with low/normal/high protein content characterize thriftiness . Methods: In this secondary cross-sectional analysis of a single-arm crossover study, 24EE was measured using whole-room indirect calorimetry during energy balance, fasting, and different overfeeding conditions (low/3% protein, high/30% protein, and 3 normal/20% protein diets) with 200% of eucaloric requirements in 77 healthy individuals [63 men; BMI (in kg/m 2 ): 26.4 ± 4.3; body fat by DXA: 27.7% ± 9.4%, mean ± SD] with normal glucose regulation. Relations between the 24EE during energy balance (adjusted for body composition) and 24EE during each overfeeding diet were analyzed using separate linear regression models. Participants were arbitrarily categorized as thrifty / spendthrift based on the median value (−177 kcal/d) of the difference in 24EE between fasting and energy balance conditions. Results: Differences in 24EE during low/high-protein overfeeding diets (regression line slope = 0.76 and 0.68, respectively, both P < 0.05 compared with slope = 1) but not during the normal-protein overfeeding diets (all P > 0.05 compared with slope = 1) were dependent on baseline 24EE during energy balance. Specifically, individuals with higher eucaloric 24EE ( thriftier phenotype) showed smaller increases in 24EE during protein-imbalanced overfeeding. Analyzed by group, thrifty individuals had smaller increases in 24EE by 42 and 237 kcal/d during low- and high-protein overfeeding, respectively, compared with spendthrift individuals who showed greater increases in 24EE by 100 and 302 kcal/d ( P ≤ 0.03 compared with thrifty group). Conclusions: During acute overfeeding conditions with low/high-protein content, thrifty participants have limited capacity to increase 24EE, indicating that impaired adaptive thermogenesis during protein-imbalanced diets further characterizes the thrifty phenotype and its susceptibility to weight gain. This trial was registered at clinicalTrials.gov as NCT00523627.